Chitosan / polyvinyl alcohol film loaded beta-acid / beta-cyclodextrin inclusion compound as well as preparation method and application thereof

By loading β-acid/β-cyclodextrin inclusions in chitosan/polyvinyl alcohol films, the non-degradability and food safety issues of plastic materials in existing food preservation technologies are solved, and efficient food preservation and environmental sustainability are achieved.

CN119899410APending Publication Date: 2025-04-29NINGXIA MEDICAL UNIVERSITY GENERAL HOSPITAL
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510214387.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the existing food preservation technology, the non-degradability of plastic materials and environmental pollution problems are difficult to meet the needs of food safety and environmental sustainability.

Method used

A chitosan/polyvinyl alcohol film-loaded β-acid/β-cyclodextrin inclusion was developed. A food packaging film with good antioxidant and antibacterial activity was prepared by incorporating β-acid and β-cyclodextrin into a chitosan/polyvinyl alcohol composite film.

Benefits of technology

This film can effectively inhibit the adhesion of pathogenic microorganisms such as Staphylococcus aureus on the surface of perishable fruits, extend the shelf life of food, and has good mechanical properties and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899410A_ABST
    Figure CN119899410A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of food preservation, and particularly relates to a chitosan / polyvinyl alcohol film loaded beta-acid / beta-cyclodextrin inclusion compound as well as a preparation method and application thereof. The method comprises the following steps: adding beta-acid / beta-cyclodextrin into distilled water, grinding and centrifuging, and freeze-drying the obtained supernatant to obtain the beta-acid / beta-cyclodextrin inclusion compound. The preparation method comprises the following steps: mixing a PVA solution with a chitosan solution, adding glycerol to obtain a mixed solution, dissolving the beta-acid / beta-cyclodextrin inclusion compound in water, adding the dissolved beta-acid / beta-cyclodextrin inclusion compound into the mixed solution, stirring, standing and drying to obtain the film. The prepared film has good physical properties and stability, has good oxidation resistance and antibacterial activity, can inhibit adhesion of pathogenic microorganisms such as staphylococcus aureus on the surfaces of perishable fruits, and prolongs the shelf life of the perishable fruits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food preservation, and in particular relates to a chitosan / polyvinyl alcohol film-loaded beta-acid / beta-cyclodextrin inclusion compound, a preparation method and an application thereof. Background Art

[0002] The safety and effective preservation of perishable fruits are currently a global concern. On the one hand, the shelf life of perishable fruits is very limited, which can easily lead to rapid loss of nutrients. On the other hand, improper consumption of spoiled fruits can cause serious health problems due to microbial contamination and may also lead to huge economic losses. For example, Staphylococcus aureus is a common foodborne pathogenic microorganism that often attaches to the surface of food and causes food poisoning. Therefore, the implementation of appropriate preservation techniques is essential to minimize resource waste and ensure food safety in the perishable food supply chain. Currently, plastic preservation materials dominate food preservation due to their cost-effectiveness, mature manufacturing process, portability and durability. However, with the increasing attention paid to food safety and environmental sustainability, the development and adoption of biodegradable and environmentally friendly materials are becoming more and more popular.

[0003] Biopolymers, especially polysaccharides, have been extensively studied for the development of biodegradable films as an alternative to conventional plastic packaging. Chitosan (CS) is a natural carbohydrate copolymer linked by β-(1-4)-glycosidic bonds, which is derived from a wide range of natural sources such as insects, plants and shells. CS has attracted increasing attention due to its advantages such as biodegradability, biocompatibility, antimicrobial activity and good film-forming ability, and can be processed into various forms such as films, fibers, sponges, gels and nanoparticles. For example, CS films have been effectively used as packaging materials, providing superior protection for various foods, including pork, strawberries, grapes and kiwifruit. However, CS films composed of only a single polysaccharide often show suboptimal mechanical properties and limited bioactivity. Therefore, many studies have gradually focused on combining two or more components to enhance the different properties of the film. Polyvinyl alcohol (PVA) is a water-soluble, nontoxic and efficient polymer that has been widely used as a matrix for food packaging films. The combination of PVA and CS to prepare composite films can greatly compensate for the mechanical properties and light transmittance of CS-based films.

[0004] Incorporating active ingredients into films can effectively address challenges associated with preserving perishable foods. Hops is a perennial plant belonging to the genus Humulus and is widely valued in the brewing industry. β-acids, an active ingredient isolated from hop extracts, have significant antimicrobial and antioxidant activities. Our previous studies have shown that incorporating β-acids as active ingredients into CS films can significantly improve the physical properties and bioactivity of CS films. However, the poor water solubility of β-acids limits their sustained efficacy. Cyclodextrins (CDs) are cyclic oligosaccharides produced by enzymatic hydrolysis of starch, which have external hydrophilicity and internal hydrophobicity. Despite great progress in the performance of composite films prepared from various materials, the development of durable food packaging films with excellent antioxidant and antimicrobial properties remains a major challenge to achieve higher levels of preservation. Therefore, it is urgent to develop a composite film with multifunctional fresh-keeping and antimicrobial properties to provide new ideas in the field of food preservation. Summary of the invention

[0005] The purpose of the present invention is to provide a chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion compound and a preparation method and application thereof. The present invention uses natural product β-acid as an active substance, prepares a β-acid / β-cyclodextrin (hydroxyethyl-β-cyclodextrin) inclusion compound, and then loads it into a chitosan / polyvinyl alcohol composite film. The prepared film has good physical properties and stability, as well as good antioxidant and antibacterial activity, can inhibit the attachment of pathogenic microorganisms such as Staphylococcus aureus on the surface of perishable fruits, and prolongs the shelf life of perishable fruits.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion compound, comprising the following steps:

[0008] (1) adding β-acid / β-cyclodextrin to distilled water, grinding and centrifuging, and freeze-drying the resulting supernatant to obtain a β-acid / β-cyclodextrin inclusion complex;

[0009] (2) dissolving polyvinyl alcohol in 50 mL of distilled water with stirring to obtain a PVA solution; dissolving chitosan in an acetic acid aqueous solution to obtain a chitosan solution;

[0010] (3) mixing the PVA solution and the chitosan solution and adding glycerol to obtain a mixed solution, and then dissolving the β-acid / β-cyclodextrin inclusion complex in water and adding it to the mixed solution to obtain a mixture;

[0011] (4) The mixture is stirred and allowed to stand to dry to obtain a film.

[0012] Furthermore, in step (1), the specific conditions of the grinding are grinding at room temperature and a frequency of 40-60 Hz for 0.5-2 h.

[0013] Furthermore, in step (1), the amount of β-acid added is 0.1-0.3 g, the amount of β-cyclodextrin added is 0.1-6 g, and the amount of distilled water added is 0.1-5 ml.

[0014] Furthermore, in step (2), the temperature at which the polyvinyl alcohol is stirred and dissolved is 60-100°C; and the temperature at which the chitosan is dissolved is 40-80°C.

[0015] Furthermore, in step (3), the amount of the PVA solution added is 30-70 mL, the amount of the chitosan solution added is 30-70 mL, and the amount of glycerol added is 0.1-2 mL.

[0016] Furthermore, in step (3), the β-acid / β-cyclodextrin inclusion complex is dissolved in 2-20 mL of water.

[0017] Furthermore, in step (4), the stirring is stirring at room temperature for 0.5-2 hours; the standing is standing for 12 hours; and the drying is drying at 25-40° C. for 24 hours.

[0018] The invention also provides a chitosan / polyvinyl alcohol film loaded beta-acid / beta-cyclodextrin inclusion compound prepared by the preparation method.

[0019] The invention also provides an application of the chitosan / polyvinyl alcohol film-loaded beta-acid / beta-cyclodextrin inclusion compound in food preservation.

[0020] Furthermore, the chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion complex can inhibit the attachment of pathogenic microorganisms such as Staphylococcus aureus to the surface of perishable fruits.

[0021] The beneficial effects of the present invention are:

[0022] β-acid is an effective ingredient from the natural plant hops. Previous studies have found that β-acid has good antioxidant and antibacterial effects. However, due to the poor water solubility and easy oxidation of β-acid, its effective function is limited. In order to improve the stability of β-acid and expand the application range of β-acid, the present invention designs a method of preparing β-acid in the form of cyclodextrin inclusion complex using a ball mill, and loading it in a chitosan-polyvinyl alcohol composite film to prepare a film that can be used for food preservation. The applicant uses infrared, scanning electron microscopy, XRD, contact angle, thermogravimetric analysis, thickness measurement, water solubility test, water content test, water vapor permeability test and other characterization techniques to verify the properties of the inclusion complex and film. In the property study, it is clear that the polysaccharide / polyvinyl alcohol film loaded with β-acid / β-cyclodextrin inclusion complex has good antioxidant properties (DPPH is 73.7%), has good antibacterial activity against Staphylococcus aureus, and the film can slowly release the active ingredients, showing a good preservation effect in the application of strawberry preservation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Figure 1 is a performance characterization diagram of β-acid / β-cyclodextrin inclusion complex, where (A) and (B) are scanning electron microscope (SEM) images; (C) and (D) are Fourier transform infrared spectroscopy (FTIR) images; (E) and (F) are ultraviolet-visible spectroscopy (UV-vis) images; (G) and (H) are β-acid, β-cyclodextrin (β-CD), physical mixture (PM) β-acid / β-CD, inclusion complex (IC) β-acid / β-CD, PM β-acid / hydroxyethyl-β-cyclodextrin X-ray diffraction (XRD) patterns of dextrin (HE-β-CD) and ICβ-acid / HE-β-CD; (I) is the 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) scavenging ability diagram of ICβ-acid / β-CD; (J) is the 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) scavenging ability diagram of ICβ-acid / HE-β-CD; (K) is the phase solubility diagram of β-acid and β-CD; (L) is the phase solubility diagram of β-acid and HE-β-CD;

[0025] Figure 2 The film characterization diagrams include: (A) SEM image; (B) film schematic diagram; (C) FTIR spectrum; (D) XRD diffraction pattern;

[0026] Figure 3 Figure 1 is the mechanical properties and thermogravimetric analysis diagram of the film, where (A) is the tensile strength of the composite film; (B) is the elongation at break of the composite film; (C) is the weight loss of the β-CD@CS / PVA film; (D) is the weight loss of the HE-β-CD@CS / PVA film; (E) is the derivative thermogravimetric analysis diagram of the β-CD@CS / PVA film; (F) is the derivative thermogravimetric analysis diagram of the HE-β-CD@CS / PVA film;

[0027] Figure 4 Figure 2 is a graph showing the release of active ingredients, where (A) and (B) are the release of β-acid from β-CD@CS / PVA film; (C) and (D) are the release of β-acid from HE-β-CD@CS / PVA film;

[0028] Figure 5 Figure 1 is the antibacterial activity diagram of the composite film, where (A) is the antibacterial effect diagram of the composite film on Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus); (B) is the SEM image of Escherichia coli and Staphylococcus aureus treated with different films; (C) is the inhibition zone of Staphylococcus aureus treated with the composite film; (D) is the DPPH free radical scavenging activity of the composite film;

[0029] Figure 6 The following is an evaluation chart of the preservation ability of the composite film, where (A) is the effect of the composite film on the storage and preservation of strawberries; (B) is the moisture loss rate of the β-CD@CS / PVA film; (C) is the growth trend of the moisture loss rate of the β-CD@CS / PVA film; (D) is the moisture loss rate of the HE-β-CD@CS / PVA film; and (E) is the growth trend of the moisture loss rate of the HE-β-CD@CS / PVA film. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] The preparation method of a chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion compound of the present invention comprises the following steps:

[0036] (1) Weigh 0.1-5 g of β-cyclodextrin / 0.1-5 g of hydroxyethyl-β-cyclodextrin, mix with 0.1-0.5 g of β-acid, and add 1-5 mL of distilled water. Grind the mixture at room temperature and 40-60 Hz for 0.5-2 h using a ball mill. After centrifugation, freeze-dry the supernatant to obtain the β-acid inclusion complex, which is stored at -20 to -40°C.

[0037] (2) Weigh 0.1-3.0g PVA, stir and dissolve it in 20-50mL distilled water at a temperature of 60-100°C to obtain a PVA solution; dissolve 0.1-3.0g CS in 20-50mL acetic acid solution, stir at 50-70°C to obtain a CS solution; mix the PVA solution and the CS solution, add 0.5-3.0mL glycerol, and dissolve 0.2-1.5g β-acid / β-cyclodextrin (hydroxyethyl-β-cyclodextrin) inclusion complex in 2-20mL H2O and add it to the CS / PVA mixed solution, stir the mixture for 0.5-2 hours, and let it stand for 12-24 hours to remove bubbles. Pour the bubble-free membrane solution into a polystyrene culture dish with a diameter of 9-10cm, and dry it at 25-40°C for 12-36 hours to obtain a film.

[0038] Example 1

[0039] Preparation of β-acid / β-cyclodextrin (hydroxyethyl-β-cyclodextrin) inclusion complex: Accurately weigh 0.17 g β-cyclodextrin / 0.2 g hydroxyethyl-β-cyclodextrin, mix with 0.12 g β-acid, and add 2 mL of distilled water. Grind the mixture at room temperature and 50 Hz for 1 h using a ball mill. After centrifugation, freeze-dry the supernatant to obtain the β-acid inclusion complex, which is stored at -20°C.

[0040] Preparation of film: accurately weigh 2.0g PVA, stir and dissolve it in 50mL distilled water at 95℃ to obtain PVA solution; dissolve 1.0g CS in 50mL acetic acid solution, stir at 70℃ to obtain CS solution; mix the PVA solution and CS solution, add 1.0mL glycerol, and dissolve 0.9g β acid / β-cyclodextrin (hydroxyethyl-β-cyclodextrin) inclusion complex in 10mL H2O and add it to the CS / PVA mixed solution, stir the mixture for 1 hour, and let it stand for 12 hours to remove bubbles. Pour the bubble-free membrane solution into a polystyrene culture dish with a diameter of 9cm, dry it at 37℃ for 24h, and obtain a film.

[0041] Example 2

[0042] Take 25 mg of the film sample prepared in Example 1 and immerse it in 10 mL of ethanol solution, store it in the dark at room temperature for 24 hours, and then add 1 mL of the extract to 3 mL of ethanol-DPPH free radical solution. The solution is reacted in the dark for 30 minutes, and the absorbance is measured at 517 nm. The absorbance value is set to zero with ethanol solution, and the ethanol DPPH free radical solution without sample is used as a control. The inhibition of DPPH is determined as follows:

[0043]

[0044] Example 3

[0045] The antibacterial activity of the composite film against Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) was evaluated by measuring the inhibition zone. First, the microorganisms were placed in a 37°C incubator for 24 hours of shaking, and then 50 μL of bacterial suspension was applied to the surface of the solid culture medium, and then a film with a diameter of 6 mm was attached to the culture medium. After culturing at 37°C for 24 hours, the growth of bacteria was observed, and the size of the antibacterial area was measured with an electronic vernier caliper with an accuracy of 0.01 mm. Then, the bacterial solution was cultured at 37°C to the logarithmic growth phase and the film sample was added for 12 hours. The treated bacteria were collected by centrifugation at 8000 rpm for 5 minutes, and after being fixed with 2.5% glutaraldehyde for 24 hours, they were gradiently dehydrated in 25%, 50%, 75%, 90%, and 100% ethanol solutions for 10 minutes. The bacterial samples taken by freeze drying were observed by scanning electron microscopy.

[0046] Example 4

[0047] The practical application of the film in preserving perishable fruits was evaluated by taking strawberries of similar quality and uniform size as the research object. The strawberries were placed in a glass cup, and the mouth of the cup was sealed with the film sample. The storage temperature of the treated strawberries was 20±3℃ and the relative humidity was 55±1%. During the storage process, the changes in the surface morphology of the fruit were photographed, and the weight was measured every two days.

[0048] (I) Physical properties characterization

[0049] The films prepared in the above implementation cases were subjected to the following tests: electron microscopy scanning, infrared spectroscopy, X-ray diffraction, thickness test, transmittance and transparency test, water content test, contact angle, thermogravimetric analysis, water vapor permeability, water solubility test, drug loading and encapsulation efficiency, release and bioactivity test.

[0050] 1. Scanning electron microscopy

[0051] Inclusion compound:

[0052] The microstructure of the mechanically prepared inclusion complex was characterized using scanning electron microscopy. Figure 1 As shown in (A): β-acid has an amorphous lamellar crystal structure; β-CD has a block structure. When they form inclusion complexes, their original structures change significantly, but physical mixing does not change their respective initial forms.

[0053] film:

[0054] like Figure 2 As shown in (A)-(B), the surface of the CS / PVA film is uniform, smooth and crack-free. The film structure is compact and the cavity is very small. Hydrogen bonds are formed between the hydroxyl and amine groups of CS and PVA, indicating that CS is compatible with PVA. The prepared β-acid inclusion complex is added to the CS / PVA film, and the film remains uniform and regular with a smooth surface. As the concentration increases, the composite film shows slight roughness and unevenness, but no cracks appear, indicating that the structure of the composite film is not damaged by surface tension during the drying process, showing excellent stability. Similar to the results of the present invention, the surface structure of the chitosan / polyvinyl alcohol film loaded with curcumin / cyclodextrin inclusion complex does not change significantly, and the surface inclusion complex can be evenly distributed in the chitosan / polyvinyl alcohol matrix. However, some studies have found that the addition of some additives can change the cross-sectional microstructure of the polymer film.

[0055] 2. Infrared spectroscopy

[0056] The inclusion complex was characterized by infrared spectroscopy. The results showed that the main infrared characteristic band of β-acid was located at 3431 cm -1 (-OH), 2973cm -1 (CH) and 1758cm -1The characteristic vibration peaks of -OH, CH, CO and COC of β-CD correspond to 3378 cm -1 (3489cm -1 )、2926cm -1 (2929cm -1 )、1025cm -1 (1028cm -1 ) and 858cm -1 (886cm -1 ). The FTIR spectrum after the inclusion complex formation showed the same absorption signal pattern as that of β-acid and inclusion complex, indicating the formation of inclusion complex. In addition, the hydroxyl groups in the β-acid structure can be placed in the cyclodextrin cavity through van der Waals interactions and hydrogen bonding. Therefore, the shift of the main absorption peak of β-acid can be seen. Through simple physical mixing, the characteristic absorption peaks of each component appeared, which is a simple spectral superposition. Therefore, the FTIR results further confirmed the interaction between β-acid and CDs, indicating the successful formation of inclusion complex.

[0057] The inclusion complex was characterized by infrared spectroscopy. The results showed that the infrared absorption spectrum of the CS / PVA composite film showed characteristic peaks of the two polymers. -1 The strong and broad absorption peak at 2906cm is caused by the stretching vibration of OH. -1 The sharp peaks at 1067 and 844 cm-1 are attributed to the CH asymmetric stretching of the remaining vinyl acetate units in the PVA backbone. -1 The peaks at 1590 cm-1 correspond to the stretching vibration of CO and the expansion vibration of CO. -1 and 1419cm -1 The peaks at 1141 cm-1 correspond to the CH and C=O stretching in CS. -1 The absorption band at 3431cm belongs to the polysaccharide structure of sugar. β-acid is the active ingredient, and its main absorption peaks are located at 3431cm of -OH, CH and C=O groups. -1 、2931cm -1 and 1758cm -1 When β-acid is added to the inclusion complex, the absorption peaks of the characteristic peaks are all shifted. After adding β-acid inclusion complex to CS / PVA film, the FTIR spectrum formed changes. It can be observed that the -NH and -OH group related bands (about 3200cm -1 ) shifted. In addition, the 0.9β-CD@CS / PVA film exhibited a higher peak intensity compared with the pure CS / PVA film, indicating a higher interaction between the polymer molecules.

[0058] 3. XRD results

[0059] The crystallinity of the film structure was studied using XRD. Figure 2 The XRD results of D show that all films exhibit an amorphous structure near 2θ = 20°, and the characteristic peak is broader. This is due to the amorphous structure of the CS and PVA films, which are unique peaks of CS and PVA. It is worth noting that after the introduction of the β-acid inclusion complex, the crystal structure of the composite film remains unchanged. In addition, the diffraction peak of β-acid is around 10°. However, with the preparation of the β-acid inclusion complex, the diffraction peak at around 20° weakened, which is consistent with the decrease in crystallinity. In other studies, it was found that the original crystallinity of CS / PVA was suppressed with the increase of the content of exogenous active ingredients.

[0060] 4. Film thickness, optical properties, water resistance and water contact angle

[0061] The results of film thickness and mechanical strength are shown in Table 1. As shown in Table 1, the thickness of the composite film ranges from 0.075 mm to 0.118 mm. The results show that there is no significant difference in the thickness of 0.1β-CD@CS / PVA, 0.3β-CD@CS / PVA, 0.1HEβ-CD@CS / PVA, 0.3HEβ-CD@CS / PVA, 0.5HEβ-CD@CS / PVA, 0.7HEβ-CD@CS / PVA, and 0.9HEβ-CD@CS / PVA films between the control films, indicating that the addition amount of β-acid / β-CD (<0.3 g, w / w) and the addition amount of β-acid / β-CD have no significant effect on the film thickness. Similarly, Huang et al. (2024) found that the addition of curcumin cyclodextrin inclusion complex to CS film did not affect the thickness. Of course, with the introduction of β-acid inclusion complex, the thickness of the film also increased. When the concentration of β-acid / β-CD is greater than 0.3 g, the film thickness increases. High concentrations of β-acid / β-CD may relax the film matrix and reduce uniformity, thereby increasing the film thickness. However, the film thickness also depends on the preparation method and drying conditions. At the same time, it is also affected by the amount of film-forming liquid.

[0062] Table 1 Thickness, contact angle, water content, water solubility, swelling degree and water vapor permeability of composite films

[0063]

[0064]

[0065] Note: Mean ± standard deviation followed by different letters in the above table indicates significant difference (p<0.05)

[0066] The applicant team further evaluated the water-related performance parameters of the composite membranes, and the results are shown in Table 1. The pure CS / PVA membrane had the highest water content of 32.00%. Interestingly, the incorporation of β-acid inclusion complex significantly reduced the water content of the composite membrane (p<0.05). On the contrary, the addition of β-acid inclusion complex increased the water solubility of the composite membrane in a concentration-dependent manner. This may be related to the fact that cyclodextrin is easily soluble in water (HE-β-CD and β-CD). In addition, the hydrophobicity test results of the composite membrane showed that the contact angle of the membrane increased with the increase of the concentration of β-acid inclusion complex. The water contact angle of the pure CS / PVA membrane was 76.50°, while the introduction of β-acid inclusion complex increased the water contact angle of the membrane surface to 110.04° and 108.59°, respectively, indicating that β-acid inclusion complex helps to enhance the hydrophobicity of the membrane, which may be due to the interaction between molecules shielding the original hydrophilic groups. The interaction of the composite membrane is promoted by hydrogen bonding, hydrophobic interactions, and electrostatic attraction between components, which contributes to the beneficial application of composite materials in the food industry.

[0067] Water vapor transmission rate (WVP) is a key parameter reflecting the barrier properties of cling film and has an important impact on the freshness and quality of packaged food. Lower WVP values ​​are associated with enhanced preservative effects and excellent resistance to water vapor barriers. The molecular weight of the film material, the degree of deacetylation of CS, the degree of hydrolysis of PVA, and the ratio of CS to PVA all affect the WVP of the film. The results showed that the concentration of β-acid inclusion complexes in the composite film significantly affected the WVP of the composite film (p<0.05) (Table 1). The addition of high concentrations of β-acid inclusion complexes increased the WVP value, which may be related to the interaction forces between the inclusion complexes.

[0068] The optical property of shielding special wavelengths is one of the important properties of food films to extend the shelf life of food. We evaluated the transmittance of the composite film by measuring the absorbance in the visible wavelength range of 250-800nm. The results are shown in Table 2. It can be observed that the absorbance of the composite film decreases with the increase of the concentration of β-acid inclusion complex. In the wavelength range of <400nm, as the cyclodextrin inclusion concentration increases, its UV transmittance decreases. This shows that the addition of inclusion complexes can make the film have better UV resistance, thereby minimizing UV-induced lipid oxidation, nutritional loss and odor. As the absorbance decreases, the transmittance of the composite film also decreases, indicating that the composite film can reduce the absorption and scattering of light and has good UV protection. In the visible light wavelength range (400-800nm), there is no significant difference in transmittance between the films, and the transmittance is all above 80%. The results show that the presence of inclusions has no effect on the transparency of the film. The absorbance at 600nm is less than 1, as shown in Table 2, indicating that the control film and the inclusion film are transparent.

[0069] Table 2 Light transmittance and transparency of CS / PVA based films

[0070]

[0071]

[0072] 5. Mechanical properties and thermogravimetric analysis of films

[0073] Tensile strength (TS) and elongation at break (EB) are the main criteria for evaluating the mechanical properties of food cling film. The strength and toughness of the film directly affect its integrity and effectiveness. Stronger mechanical properties can effectively avoid and reduce external pressure on food. Figure 3 A and Figure 3 B shows that the TS and EB of pure CS / PVA film are 6.60MPa and 98.41%, respectively. The addition of β-acid inclusion complex significantly improves the toughness of CS / PVA-based films. This trend indicates that the functional groups of the inclusion complex increase the interaction between CS and PVA and enhance the cohesion of the film matrix. When the concentration of β-acid inclusion complex / HE-β-CD inclusion complex is 0.3g, the TS of the composite film is the highest, which is 123.10MPa. The increase in the interaction strength of each component will promote the improvement of the pull-up strength of the film. The cyclodextrin rich in hydroxyl groups on the surface forms multiple interfacial hydrogen bonds, and due to the specific constraint effect, a physical network structure is formed, which is helpful for the encapsulation and blocking of β-acid. Conventional food packaging standards generally require TS to be above 3.5MPa, so the composite film prepared by the present invention meets the standards.

[0074] The thermal stability of the film was determined by a thermogravimetric analyzer. The weight loss of the film samples in different temperature ranges was analyzed to determine the thermal stability of the film. Figure 3 As shown in Figures C-3E and 3D-3F, the weight loss of all composite membranes in the temperature range of 30℃ to 800℃ was recorded. In the temperature range of 100~180℃, the weight of the composite membrane decreased rapidly due to the evaporation of water from the composite membrane. From 200℃ to 350℃, the mass loss was caused by the breaking of covalent bonds and the depolymerization of macromolecular substances. The composite membrane loaded with β-acid inclusion complex has a higher degradation temperature, indicating that it has higher thermal stability. The thermal stability of 0.9β-CD@CS / PVA and 0.9HE-β-CD@CS / PVA composite membranes is higher than that of other composite membranes.

[0075] 6. Active ingredient release test

[0076] The active ingredient β-acid is effectively released from the membrane, playing an antioxidant and antibacterial role. This experiment revealed the release of β-acid at pH = 2, 6.8 and 7.4. In addition, the cumulative percentage of β-acid released from the membrane is shown in Figure 4 The release of β-acid from the film follows a biphasic kinetic: a relatively fast release followed by a slow release. Figure 4As shown in Figures A and 4C, the release of β-acid is more rapid in the initial release phase and continues to slow in the later stable phase. In general, the factors that control the release of β-acid from the membrane include the degree of hydration and solubilization of the matrix, the mechanism of interaction between the polymer and the compound, the material and thickness of the membrane, and the type of release system used. First, due to the extensive penetration of the buffer in the membrane, β-acid exhibits a rapid release period, which increases the diffusion area of ​​the inclusion complex through the membrane. The sustained release phase of the drug may be due to the encapsulation of β-acid in the polymer matrix. The penetration of the buffer into the inclusion complex causes the inclusion complex to dissolve and the β-acid to diffuse out of the membrane. As the pH value decreases, the cumulative release of β-acid decreases. Over time, the release of β-acid in the buffer is the highest at pH = 7.4. In fact, the host and guest molecules in the inclusion complex interact through non-covalent bonds such as van der Waals forces and hydrogen bonds, and are usually more stable in a neutral environment, which is conducive to the gradual dissociation and release of the inclusion complex. In general, β-acid can be effectively and slowly released from the film, providing a basis for the lasting freshness of food.

[0077] 7. Antibacterial activity of composite films

[0078] Antibacterial activity is an important indicator for preventing harmful microorganisms from contaminating food. Usually, substances with antibacterial properties are added to the film to enhance its antibacterial properties. The antibacterial activity of the composite film against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) was evaluated by measuring the inhibition zone. Figure 5 A. Figure 5 B and Figure 5 The results of C show that the composite membrane has a better antibacterial effect on Staphylococcus aureus than Escherichia coli. Among them, the pure CS / PVA membrane has no antibacterial activity. The composite membranes (0.1β-CD@CS / PVA, 0.3β-CD@CS / PVA; 0.1HE-β-CD@CS / PVA, 0.3HE-β-CD@CS / PVA) also have no antibacterial activity, which may be related to the low concentration of inclusion complexes in the composite membranes. In summary, the β-CD@CS / PVA membrane has a good antibacterial effect, and it exhibits an antibacterial effect when the ICβ-acid / β-cd concentration is ≥0.5g. However, when the ICβ-acid / HE-β-cd concentration is 0.7g, the HE-β-CD@CS / PVA membrane exhibits bacterial inhibition with a smaller inhibition zone. This may be related to the slow release of β-acid caused by different CD structures. At pH=7.4, the release of β-acid in the 0.9β-CD@CS / PVA membrane is higher than that in the 0.9HE-β-CD@CS / PVA membrane. Unfortunately, the composite membrane showed no inhibitory activity against E. coli. Based on the inhibitory effect of β-acid on E. coli, we inferred that the membrane was loaded with a low concentration of β-acid inclusion complex, which did not reach the sterilizing concentration.

[0079] Secondly, the morphology of Staphylococcus aureus and Escherichia coli after being treated with different films. Scanning electron microscope images showed surface wrinkles and ruptured dead bacteria ( Figure 5 B). 0.9β-CD@CS / PVA membrane and 0.9HE-β-CD@CS / PVA membrane caused significant damage to the structure of Staphylococcus aureus. In contrast, due to the low content of β-acid active ingredients in the membrane, Escherichia coli only showed surface damage, and no structural damage to E. coli was observed. The results show that cyclodextrin inclusion complexes can effectively inhibit the activity of foodborne pathogens (Staphylococcus aureus) and have the potential to extend the shelf life of food.

[0080] 8. Antioxidant properties of the film

[0081] The antioxidant properties of films are usually evaluated by DPPH free radical scavenging rate. The results showed that the scavenging rate of DPPH free radicals by CS / PVA film was the lowest (5.56%) ( Figure 5 D). Interestingly, the addition of β-acid inclusion complex significantly improved the antioxidant properties of the composite films, with the highest antioxidant properties (72.98% and 73.47%). As the concentration of β-acid inclusion complex in the composite film increased, the antioxidant capacity of the composite film gradually increased. This result is consistent with the antioxidant results of β-acid inclusion complex. The unique structure of β-CD and HE-β-CD promotes the encapsulation of β-acid and enhances the stability and antioxidant activity of the guest molecule. The scavenging ability of the composite film for free radicals is mainly reflected in the DPPH free radical, which is an organic nitrogen free radical containing an unsaturated double bond. The hydrogen atoms obtained when reacting with antioxidants will neutralize the DPPH free radical, thereby reducing or preventing the oxidation reaction. Films containing antioxidants can be effectively used to package foods that are easily oxidized. This method can not only prevent food oxidation, but also help to extend the shelf life of food.

[0082] 9. Evaluation of the preservation performance of perishable fruits

[0083] Strawberries were used as the research object to evaluate the ability of composite films to preserve perishable fruits. The changes in the surface and water loss rate of strawberries after 8 days of storage were observed and recorded. Figure 6As shown in A, the untreated strawberries showed epidermal rupture as early as the 4th day, and a large amount of mold formed on the 6th day. The strawberries treated with CS / PVA film showed slight epidermal damage on the 6th day, and mold formed on the 8th day. The β-acid inclusion complex-doped composite film can effectively inhibit strawberry mold contamination. The results showed that the composite film (0.3, 0.5, 0.7, 0.9β-CD@CS / PVA) can effectively inhibit strawberry mold contamination and extend the shelf life of strawberries by 8 days without obvious skin damage. The composite film (0.5, 0.7HE-β-CD@CS / PVA) has a better preservation effect. Compared with the β-CD@CS / PVA film, the HE-β-CD@CS / PVA film has poor freshness preservation, which is consistent with the results of poor antioxidant and antibacterial activity.

[0084] Water loss rate is an important indicator for evaluating the quality characteristics of strawberries. The results showed that the final water loss rate of strawberries without film treatment was 50.48%, while the final water loss rate of strawberries treated with CS / PVA film was 35.97% ( Figure 6 B. Figure 6 C. Figure 6 D. Figure 6 E). The strawberries treated with β-CD@CS / PVA film and HE-β-CD@CS / PVA film had the lowest water loss rates, which were 21.62% and 24.17%, respectively. This result is also consistent with the results of the surface preservation effect of strawberries. In summary, β-CD@CS / PVA film and HE-β-CD@CS / PVA film have the effects of preventing water loss in perishable fruits, reducing the dehydration rate, and extending the shelf life of fruits. β-CD@CS / PVA film has good freshness preservation.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A method for preparing a chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion compound, characterized in that: The following steps are involved: (1) adding β-acid / β-cyclodextrin to distilled water, grinding and centrifuging, and freeze-drying the resulting supernatant to obtain a β-acid / β-cyclodextrin inclusion complex; (2) dissolving polyvinyl alcohol in 50 mL of distilled water with stirring to obtain a PVA solution; dissolving chitosan in an acetic acid aqueous solution to obtain a chitosan solution; (3) mixing the PVA solution and the chitosan solution and adding glycerol to obtain a mixed solution, and then dissolving the β-acid / β-cyclodextrin inclusion complex in water and adding it to the mixed solution to obtain a mixture; (4) The mixture is stirred and allowed to stand to dry to obtain a film.

2. The preparation method according to claim 1, characterized in that In step (1), the specific conditions of the grinding are grinding at room temperature and a frequency of 40-60 Hz for 0.5-2 h.

3. The preparation method according to claim 1, characterized in that: In step (1), the amount of β-acid added is 0.1-0.2 g, the amount of β-cyclodextrin added is 0.1-6 g, and the amount of distilled water added is 0.1-5 ml.

4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the polyvinyl alcohol when being stirred and dissolved is 60-100°C; the temperature of the chitosan when being dissolved is 40-80°C.

5. The preparation method according to claim 1, characterized in that: In step (3), the amount of the PVA solution added is 30-70 mL, the amount of the chitosan solution added is 30-70 mL, and the amount of glycerol added is 0.1-2 mL.

6. The preparation method according to claim 1, characterized in that: In step (3), the β-acid / β-cyclodextrin inclusion complex is dissolved in 2-20 mL of water.

7. The preparation method according to claim 1, characterized in that: In step (4), the stirring is stirring at room temperature for 0.5-2 hours; the standing is standing for 12 hours; and the drying is drying at 25-40° C. for 24 hours.

8. A chitosan / polyvinyl alcohol film loaded with β-acid / β-cyclodextrin inclusion complex prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the chitosan / polyvinyl alcohol film-loaded β-acid / β-cyclodextrin inclusion compound as claimed in claim 8 in food preservation.

10. The use according to claim 9, characterized in that The chitosan / polyvinyl alcohol film-loaded beta-acid / beta-cyclodextrin inclusion compound can inhibit the attachment of pathogenic microorganisms such as Staphylococcus aureus on the surface of perishable fruits.

Citation Information

Cited By

  • Light-proof sterile packaging bag and preparation method thereof

    CN120680788A

  • Photoresponsive Cu-WVP-PC composite film as well as preparation method and application thereof

    CN120699300A